Long-Term Survival Outcomes after Coronary Artery Revascularization Surgery of Bangladeshi Population: A Single Centre Study (Ibrahim Cardiac Medical Journal, 2020)
Background & objective : Coronary artery bypass graft (CABG) surgery has given symptomatic and structural release of coronary atherosclerotic heart disease. CABG has been performed frequently for more than 30 years in Bangladesh. But there are no nationwide studies on the rate of survival in Bangladesh. The present study was undertaken to find the post CABG surgery survival outcomes and association between risk factors and survival over long time span.Methods: We studied 650 consecutive patients’ post-operative clinical data retrospectively and survival outcome data were collected prospectively who had CABG surgery from 2010 to 2015 in Ibrahim Cardiac Hospital & Research Institute. Of the 650 patients, 84(12.9%) died after a median follow up of 4.9 years. Demographic, clinical, operative and postoperative characteristics were then compared between survived and died patients to find the factors associated with survival.Result: Analysis revealed that younger patients were more likely to survive [RR = 1.1(95% CI = 1.0-1.2)] longer than those who have had their CABG at or > 55 years (p = 0.001). Males generally had a higher likelihood of survival [RR = 1.1(RR = 1.1(95% CI = 0.9-1.2)] than their female counterparts (p = 0.038). Non-diabetics tend to have a better survival [RR = 2.3(95% CI = 1.3-3.9)] than diabetics (p = 0.001). Non-smokers also have a higher chance of longer survival [RR = 1.5(95% CI = 0.9-2.2)] than the smokers. CABG patients without CKD enjoyed longer survival [RR = 1.4(95% CI = 0.9-2.2)] than CABG patients with CKD (p = 0.006). None of the operative and postoperative factors but hospital stay was associated with longer survival. The survived patients had a shorter mean hospital stay than the patients who died (p = 0.001). Analyses of the causes of death revealed heart disease to be the predominant cause (38%) followed by stroke (12%), CKD (8%) and other causes like cancer, liver disease etc. (42%).Conclusion: Younger, male, non-smoker, non-diabetic patients may enjoy long-term survival following CABG surgery. Prediction of long-term survival can be used to determine the most appropriate post-discharge care strategies. This would undoubtedly help both patients and doctors to implement behavioral and therapeutic modifications to optimize benefit from surgery.Ibrahim Card Med J 2019; 9 (1&2): 8-15